A hybrid Firefly Algorithm using genetic operators for the cryptanalysis of a monoalphabetic substitution cipher - Luthra, J.; Pal, S. K. (2011 World Congress on Information and Communication Technologies, 2011)
The monoalphabetic substitution cipher encrypts a given text by replacing every letter in the text with a different letter according to some predefined scheme. The cryptanalysis of this cipher involves the identification of this scheme using known language statistical data. The firefly algorithm (FA) is a metaheuristic algorithm, inspired by the flashing behavior of fireflies. This paper discusses the integration of the operators of mutation and crossover commonly used in Genetic Algorithms with the Firefly Algorithm for cryptanalysis of the monoalphabetic substitution cipher.